GeoGebra as a Visualization Tool: Implications for Mathematics Anxiety in Analytical Geometry Lectures - Aba, Maria Martini; Cholily, Yus Mochamad; Baiduri, Baiduri; Inganah, Siti; Wula, Zainur; Rahardjanto, Abdulkadir (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2025)
This study investigates the impact of using GeoGebra as a geometric visualization tool on reducing mathematics anxiety among students in a Mathematics Education program. GeoGebra, an interactive software, enables dynamic visualization of geometric concepts, potentially fostering deeper conceptual understanding and alleviating anxiety in learning mathematics. A one-group pretest-posttest design was employed, consisting of three phases: preparation, implementation, and data analysis. Data were collected through a mathematics anxiety questionnaire administered before and after the intervention using Google Forms. The participants were 45 Mathematics Education students enrolled in an Analytical Geometry course. Data analysis involved tests of normality, homogeneity, and a paired sample t-test. The results indicate that: (1) GeoGebra effectively reduces students' anxiety in learning geometry; (2) its interactive visualizations enhance conceptual understanding and mitigate anxiety levels; (3) there is a statistically significant difference in anxiety levels before and after the use of GeoGebra; and (4) students reported a more enjoyable and less stressful learning environment, which increased their engagement with the course content. These findings suggest that integrating GeoGebra into geometry instruction can be a valuable pedagogical strategy for reducing mathematics anxiety and promoting meaningful learning experiences